Reflections on the international impact of Chinese STM journals. Issue 2 (1st October 2018) - Zhang, Yuehong (Helen); Bao, Fang; Wu, Jian; Lin, Hanfeng
Abstract : There are 5, 020 scientific, technical and medical (STM) periodicals, including 548 English‐language (E‐L) journals, in China. To quickly increase the international influence of Chinese journals, government management launched significant initiatives for publishers, such as the 'Project for Enhancing International Impact of China STM Journals (PIIJ, 2013–2018)'. This paper investigates the underlying objectives and assumptions made about the value and impact of Chinese E‐L journals and the effect of PIIJ support and international publisher collaboration. The authors conclude that, while the E‐L journals are demonstrating some quantifiable improvements in internationalization, there are no equal pressures or recognition for qualitative quality measures, and this may undermine the ability of Chinese E‐L journals to build sustainable strategic plans.